2021
DOI: 10.3390/ma14040968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modification of Amorphous Silica with Ammonium Agents on the Physicochemical Properties and Hydrogenation Activity of Ir/SiO2 Catalysts

Abstract: The modification of commercial silica with solutions of NH4F or NH4Cl salts, followed by thermal treatment, enabled generation of the acidic sites in SiO2 and changed its textural properties. The use of ammonium salts solution also caused the generation of additional porosity. Using NH4F solution caused significant decrease in the specific surface area and the increase in the average pore diameter. The number and strength of resulting acid sites depend on the nature of anion in the applied ammonium salt and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The BET surface area, pore sizes and pore volumes data of C2@SBA‐15 and C3@SBA‐15 were calculated from N 2 adsorption–desorption isotherms (Figure S31). The nitrogen sorption analysis suggested that both supported catalysts showed type IV isotherms, which is a characteristic of mesoporous materials 50 . Compared with the SBA‐15, the anchored molecular complexes exhibited a clear decrease in the BET surface areas and pore volumes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The BET surface area, pore sizes and pore volumes data of C2@SBA‐15 and C3@SBA‐15 were calculated from N 2 adsorption–desorption isotherms (Figure S31). The nitrogen sorption analysis suggested that both supported catalysts showed type IV isotherms, which is a characteristic of mesoporous materials 50 . Compared with the SBA‐15, the anchored molecular complexes exhibited a clear decrease in the BET surface areas and pore volumes.…”
Section: Resultsmentioning
confidence: 97%
“…The nitrogen sorption analysis suggested that both supported catalysts showed type IV isotherms, which is a characteristic of mesoporous materials. 50 Compared with the SBA-15, the anchored molecular complexes exhibited a clear decrease in the BET surface areas and pore volumes. Pure SBA-15 showed a specific surface area of 433 m 2 /g, a pore volume of 0.705745 cm 3 /g and an average pore size of 65.08 nm.…”
Section: Synthesis and Characterisation Of Ligandmentioning
confidence: 95%
“…The BET surface area values (Figure 5c) were 21.95 m 2 /g, 10.799 m 2 /g, and 20.106 m 2 /g for 1% Ag-ZnO-CSs, 1% Au-ZnO-CSs, and 20/80 ZnO-CSs, respectively. The adsorption-desorption isotherms of 1% Ag-ZnO-CSs (Figure 5a) can be categorised as a typical type IV isotherm with a hysteresis loop H3 in accordance with IUPAC nomenclature, indicating a purely mesoporous material with small pore sizes [74][75][76]. The isotherms for 1% Au-ZnO-CSs and 20/80 ZnO-CSs exhibited hysteresis loops of type H2 (Figure 5a), indicating a mixture of macropores and mesopores [77,78].…”
Section: N 2 Adsorption-desorption Studies Bjh Pore Volume and Surfac...mentioning
confidence: 88%
“…Higher concentrations of urea, such as in our cementation solution, have been shown to be toxic and inhibit growth of E. coli (Weinstein and McDonald, 1945;Schlegel et al, 1961;Taabodi et al, 2019). Alternatively, it is possible that the high levels of urea and ammonium chloride introduce porosity into the biomineralized silica structure (Kot et al, 2021), thereby weakening the biocementation product. In spite of this, cementation solution was applied to E. coli INP-silicatein-α as with S. pasteurii, to ensure that comparisons between the unconfined compressive strength could be credited to the different E. coli INP-silicatein-α and S. pasteurii microbes.…”
Section: Discussionmentioning
confidence: 99%